Long-term Outcomes of Patients With Giant Intracranial Arteriovenous Malformations. Issue 1 (July 2016) - Yang, Wuyang; Wei, Zhikui; Wang, Joanna Y.; Hung, Alice L.; Caplan, Justin M.; Braileanu, Maria; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Huang, Judy
Abstract : BACKGROUND: Giant intracranial arteriovenous malformations (AVMs) are rare cerebrovascular lesions that pose management challenges. OBJECTIVE: To further clarify outcomes in patients with giant cerebral AVMs managed with conservative or interventional therapies. METHODS: We performed a retrospective review of all patients diagnosed with AVMs evaluated at our institution from 1990 to 2013. Patients with a single intracranial AVM >6 cm were included. Patients were divided into 2 groups: conservative management or intervention (microsurgery, radiosurgery, or embolization). Functional outcome was assessed with the modified Rankin Scale (mRS) and compared between the 2 groups. RESULTS: A total of 55 patients with giant AVMs were included, and 35 patients (63.6%) had clinical follow-up with a mean of 11.8 years. Spetzler-Martin grades were as follows: grade III, n = 2 (3.6%); grade IV, n = 15 (27.3%); and grade V, n = 38 (69.1%). Twenty-four patients (43.6%) were conservatively managed. The patients in the conservatively managed group had larger AVMs ( P < .05) with more frequent involvement of the temporal lobe ( P = .02). Five patients (26.3%) in the conservatively managed group and 5 (31.3%) in the intervention group experienced hemorrhage during follow-up, translating to an annualized risk of 2.7% and 4.1%, respectively. No significant difference in risk of first subsequent hemorrhage was observed ( P = .78). Despite comparable mRS scores at presentation, we observed a trend toward better outcomes (mRS < 2) in patients undergoing conservative management ( P = .06) compared with the intervention group at last follow-up. CONCLUSION: This study suggests that interventions for giant AVMs should be considered cautiously because hemorrhagic risk is similar regardless of management strategy and functional outcome is likely to be same or better in the conservatively managed population. ABBREVIATIONS: AVM, arteriovenous malformation mRS, modified Rankin Scale Abstract : Supplemental Digital Content is Available in the Text.